Tryptophan metabolism as bridge between gut microbiota and brain in chronic social defeat stress-induced depression mice - Xie, Jing; Wu, Wen-tao; Chen, Jian-jun; Zhong, Qi; Wu, Dandong; Niu, Lingchuan; Wang, Sanrong; Zeng, Yan; Wang, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
Backgrounds: Gut microbiota plays a critical role in the onset and development of depression, but the underlying molecular mechanisms are unclear. This study was conducted to explore the relationships between gut microbiota and host’s metabolism in depression. Methods: Chronic social defeat stress (CSDS) model of depression was established using C57BL/6 male mice. Fecal samples were collected from CSDS group and control group to measure gut microbiota and microbial metabolites. Meanwhile, tryptophan metabolism-related metabolites in hippocampus were also analyzed. Results: CSDS successfully induced depressive-like behaviors in CSDS group. The 24 differential bacterial taxa between the two groups were identified, and 14 (60.87%) differential bacterial taxa belonged to phylum Firmicutes. Functional analysis showed that tryptophan metabolism was significantly affected in CSDS mice. Meanwhile, 120 differential microbial metabolites were identified, and two key tryptophan metabolism-related metabolites (tryptophan and 5-hydroxytryptophan (5-HTP)) were significantly decreased in feces of CSDS mice. The correlation analysis found the significant relationships between tryptophan and differential bacterial taxa under Firmicutes, especially genus Lactobacillus (r=0.801, p=0.0002). In addition, the significantly decreased 5-hydroxytryptamine (5-HT) in hippocampus of depressed mice was also observed. Conclusions: Our results showed that tryptophan metabolism might have an important role in the crosstalk between gut microbioa and brain in depression, and phylum Firmicutes, especially genus Lactobacillus, might be involved in the onset of depression through regulating tryptophan metabolism.